PENERAPAN VIRTUAL LABORATORY BASED AUGMENTED REALITY TERINTEGRASI MEDIA ANDROID UNTUK GURU SMA NEGERI 10 MAROS - Nasrullah, Ince; Rusdi, Hikmah; Kasmawati, Kasmawati (Smart Education, 2024)
Abstract: This community service activity aims to improve learning facility services, namely Indonesian language practicum and improve the ability of Indonesian language teachers to utilize technology for more effective learning at SMA Negeri 10 Maros which is located around the Maros Muslim University area. This training and mentoring was carried out for 15 subject area teachers who focused on introducing and implementing the Assemblr Edu (AR) application which was designed to make the teaching and learning process more interactive and interesting. This service activity succeeded in empowering teachers with the technological skills needed to create a more interactive and effective learning experience. Despite experiencing a challenge that was successfully overcome through various solutions implemented. Technological facilities are provided, training is designed flexibly and ongoing support via online platforms. A WhatsApp group is provided to help participants. The results of this activity have empowered teachers with the skills necessary to effectively integrate technology into teaching methods, as well as improving the quality of learning experiences for students in the digital era. Keywords: training and mentoring; AR application technology; teachers. Abstrak: Kegiatan pengabdian masyarakat ini, bertujuan untuk meningkatkan pelayanan fasilitas pembelajaran, yaitu praktikum bahasa Indonesia dan meningkatkan kemampuan guru bahasa Indonesia dalam memanfaatkan teknologi untuk pembelajaran yang lebih efektif di SMA Negeri 10 Maros yang berlokasi di sekitar wilayah Universitas Muslim Maros. Pelatihan dan pendampingan ini dilaksanakan bagi 15 guru bidang studi mata pelajaran yang fokus pada pengenalan dan penerapan aplikasi Assemblr Edu (AR) yang dirancang untuk membuat proses belajar mengajar lebih interaktif dan menarik. Kegiatan pengabdian ini berhasil memberdayakan guru dengan keterampilan teknologi yang dibutuhkan untuk menciptakan pengalaman belajar yang lebih interaktif dan efektif. Meskipun mengalami suatu tantangan yang berhasil diatasi melalui berbagai solusi yang diterapkan. Fasilitas teknologi disediakan, pelatihan dirancang fleksibel dan dukungan berkelanjutan melalui platform online. WhatsApp group disediakan untuk membantu peserta. Hasil dari kegaiatan ini telah memberdayakan guru dengan keterampilan yang diperlukan untuk mengintegrasikan teknologi secara efektif ke dalam metode pengajaran, serta meningkatkan kualitas pengalaman belajar bagi siswa di era digital. Kata kunci: pelatihan dan pendampingan; teknologi aplikasi AR; guru.